المدرسة وتعاظم دورها في المجتمع المعاصر - يحياوي, نجاة (Sciences humaines; Vol. 37 (2014): SCIENCES HUMAINES(Novembre))
تعتبر المدرسة من أهم المؤسسات الاجتماعية التي تعمل على تهيئة الاجيال بالتربية والعلم ليساهموا في تنمية المجتمع وتقدمه، ولقد تعاظم دور المدرسة عبر الزمن، ومع التغيرات الاجتماعية والتسارع العلمي تواجه المدرسة تغيرات وتحديات في وظائفها، التي أخذت أبعادا مختلفة وهذا دليل على أن دور المدرسة يزداد أهمية ويتطلب مشاركة فعالة للأفراد والمؤسسات الاجتماعية، ويجب على المدرسة أن لا  تكون بمعزل عن المجتمع وأن يتم التخطيط لوظائفها وصول إلى الأهداف التي يسعى         إلى تحقيقها النظام التربوي.  يوجد العديد من  مصادر التعليم والمعرفة ولكن تبقى المدرسة تمارس دورها التعليمي، ويجب أن تكون على استعداد للمزيد من التطور و التغيير دائما . School is the most important social institutions that work to creating  generations of knowledge and  science to contribute to the development and progress of society, by the times the role of the school growing over time, and with the social changes and the acceleration of scientific, the school  facing changes in it’s role, the role of school took different dimensions which indicates that this role has became increasingly important and requires active participation of individuals and social institutions, so the school must not be in isolation from the society and to plan for its role to achieve the goals of  the educational system.  There are many sources of  knowledge and education, but the school always remains the education role , it should be ready for further development and change always.